Worker exploitation in the case of food delivery platforms in China - Zhang,Jiale; Gong,Yiyun (2024)
This thesis investigates labor exploitation within China's food delivery industry, focusing on dominant platforms such as Meituan and Eleme amid the rapid growth of the digital economy. The study is motivated by concerns about the working conditions of delivery workers, who often lack formal contracts and protections, leaving them vulnerable to exploitation, especially through the use of algorithmic management systems by these platforms. Through a qualitative approach involving interviews with delivery workers, this research aims to identify and analyze specific instances of exploitation faced by these workers and understand the underlying reasons behind these practices within China's evolving digital landscape. The findings contribute to a deeper understanding of labor exploitation dynamics in the context of the gig economy and platform-based work, with practical implications for improving labor rights and protections in the food delivery sector.
Keywords: Labor Exploitation; Food Delivery Industry; Gig Economy; Platform Economy; Algorithmic Management; China; Meituan; Eleme